In vivo Implantation of a Bovine-Derived Collagen Membrane Leads to Changes in the Physiological Cellular Pattern of Wound Healing by the Induction of Multinucleated Giant Cells: An Adverse Reaction? - Al-Maawi, Sarah; Vorakulpipat, Chakorn; Orlowska, Anna; Zrnc, Tomislav A.; Sader, Robert A.; Kirkpatrick, C James; Ghanaati, Shahram (Frontiers in Bioengineering and Biotechnology, 2018)
The present study evaluated the tissue response towards a resorbable collagen membrane derived from bovine achilles tendon (test group) in comparison to physiological wound healing (control group). After subcutaneous implantation in Wistar rats over 30 days, histochemical and immunohistochemical methods elucidated the cellular inflammatory response, vascularization pattern, membrane protein and cell absorbance capacity. After 30 days, the test-group induced two different inflammatory patterns. On the membrane surface, multinucleated giant cells (MNGCs) were formed after the accumulation of CD-68-positive cells (macrophages), whereas only mononuclear cells (MNCs) were found within the membrane central region. Peri-implant vascularization was significantly enhanced after the formation of MNGCs. No vessels were found within the central region of the membrane. Physiological wound healing revealed no MNGCs at any time point. These dynamic changes in the cellular reaction and vascularization within the test-group are related typical indications of a foreign body reaction. Due to the membrane-specific porosity, mononuclear cells migrated into the central region, and the membrane maintained its integrity over 30 days by showing no breakdown or disintegration. The ex vivo investigation analyzed the interaction between the membrane and a blood concentrate system, liquid platelet-rich fibrin (liquid PRF), derived from human peripheral blood and consisting of platelets, leukocytes and fibrin. PRF penetrated the membrane after just 15 min. The data question the role of biomaterial-induced MNGCs as a pathological reaction and whether this is acceptable to trigger vascularization or should be considered as an adverse reaction. Therefore, further pre-clinical and clinical studies are needed to identify the types of MNGCs that are induced by clinically approved biomaterials.